FDT2 Based Flow Configuration Software on IIoT Environment. Issue 4 (1st July 2019) - Ito, Akio; Sin Wai Chan, Jason
Abstract : This paper presents flow configuration software enhancement on the industrial internet of things (IIoT) environment using field device tool (FDT) ver. 2 (FDT2) technology. The focus of this paper is to exhibit how FDT2 business logic components are preserved for IIoT enhancement and how easily IIoT environment is realized. We show the value of this development by explaining the effectiveness of IIoT use cases. The FDT IIoT server (FITS) and the reference architecture model Industrie 4.0 (RAMI 4.0) relation analysis is done to prove its effectiveness. We confirmed a dramatical change of field device management work by each use case analysis which covers a variety of end-user requirement. Decoupling the DTM user interface and DTM business logic means that digital data produced in DTM business logic is transformed appropriately according to each end-user scenario. We decoupled flow measurement application extended functionality, and it means that achievement in developing key technologies for an asset management tool that makes full use of IIoT to measure mass flow.